Profiling of mitochondrial heteroplasmy in single human oocytes by next‐generation sequencing. Issue 12 (29th November 2022) - Russo, Valentina; Ancora, Massimo; Gatta, Valentina; Orsini, Massimiliano; Prencipe, Giuseppe; Peserico, Alessia; Colosimo, Alessia; El Khatib, Mohammad; Mauro, Annunziata; Di Berardino, Chiara; Scialabba, Silvia; Tiboni, Gian Mario; et al.
Abstract: Mitochondrial DNA (mtDNA) plays a crucial role in the development of a competent oocyte. Indeed, mtDNA alterations may predispose to chromosome nondisjunction, resulting in infertility due to a reduced vitality and quality of oocytes and embryos. In this methods paper, the multiple displacement amplification approach was applied in combination with next‐generation sequencing (NGS) to amplify and sequence, in single‐end, the entire mtDNA of single human oocytes to directly construct genomic NGS libraries, and subsequently, to highlight and quantify the mutations they presented. The bioinformatic workflow was carried out with a specific ad hoc developed in‐house software. This approach proved to be sensitive and specific, also highlighting the mutations present in heteroplasmy, showing deletion, insertion or substitution mutations in the genes involved in the respiratory chain, even if the found variants were benign or of uncertain meaning. The analysis of mtDNA mutations in the oocyte could provide a better understanding of specific genetic abnormalities and of their possible effect on oocyte developmental competence. This study shows how this approach, based on a massive parallel sequencing of clonally amplified DNA molecules, allows to sequence the entire mitochondrial genome of single oocytes in a short time and with a single analytical run and to verify mtDNA mutations.